VALIDITY OF STUDENT WORKSHEET BASED GUIDED INQUIRY ON VIBRATION AND WAVE MATERIALS TO TRAIN CRITICAL THINKING SKILLS - Putri Wahyu Ramadhani; An Nuril Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aims to describe validity of Student Worksheets based on guided inquiry learning on vibration and wave material to train junior high school student’s critical thinking skills. This student worksheets was developed using ADDIE model. The results was obtained from validation by two science expert lecturer and a science teacher of junior high school which obtained mode score of 4 with valid criteria at all aspect i.e. Content suitability, presentment suitability, terms suitability, and student worksheets based on guided inquiry suitability. Based on the results of this study, it can be concluded that validity of student worksheets based on guided inquiry valid to train student critical thinking skills.Keywords : Student Worksheets, Guided Inquiry, and Critical Thinking Skills.